2021
DOI: 10.1016/j.jmh.2021.100062
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of international migrant workers amidst large-scale dormitory outbreaks of COVID-19: A population survey in Singapore

Abstract: Introduction Worldwide, COVID-19 clusters have emerged within communities of international migrant workers operating in high-density work and living environments. Despite their increased vulnerability, no study has documented the mental health burden of COVID-19 amongst these groups. To address this gap, we conducted a survey of migrant workers involved in large-scale dormitory outbreaks within Singapore. Methods Between 22 June to 11 October 2020, questionnaires were d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 18 publications
1
20
1
Order By: Relevance
“…Our findings align with existing studies of migrant worker prepandemic and during COVID-19 times,8 9 22–26 yet drill down explicitly to illustrate insights from Indian and Bangladeshi migrant workers on mental health related experiences under dormitory lockdown. Identified sources of tension and solutions can be best understood, overarchingly, when mapped according to the socioecological model (see figure 3).…”
Section: Discussion and Recommendationssupporting
confidence: 82%
See 2 more Smart Citations
“…Our findings align with existing studies of migrant worker prepandemic and during COVID-19 times,8 9 22–26 yet drill down explicitly to illustrate insights from Indian and Bangladeshi migrant workers on mental health related experiences under dormitory lockdown. Identified sources of tension and solutions can be best understood, overarchingly, when mapped according to the socioecological model (see figure 3).…”
Section: Discussion and Recommendationssupporting
confidence: 82%
“…A study of infected migrant workers in recovery in a mass quarantine facility in Singapore showed that major stressors were the inability to continue providing for families and feeling susceptible to infection in crowded dorms 8. Another study examining the mental health burden of migrant workers involved in movement restrictions between June and October 2020 via online and in-person surveys showed that the overall level of mental health was on par with the rest of the community 9…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The respondents in the current study reported higher values in depression and stress when compared to stranded citizens/permanent residents, who scored 64.2%, 64.4% and 41.7% respectively for depression, anxiety, and stress. Furthermore, when compared to DASS in the published COVID-19 studies and especially in studies focused on migrant workers (23-25), healthcare workers (20) or the general population (19, 21, 26), the scores of the present study are dramatically higher, over 50% more severe in some cases. Along with research indicating that those negatively impacted by Australian international border closures were at an increased risk of elevated psychological distress (27), these scores combined provide additional evidence that travel restrictions have negative psychological consequences towards those directly impacted by them.…”
Section: Discussionmentioning
confidence: 66%
“…While cordons sanitaires was effective in preventing spillover of infection back into the general population which was the ultimate goal of the approach. However, the length of lockdown in crowded conditions, and restrictions that lasted over a year on their social activities and freedom to go to third places beyond their work or home, had been reported to have a deleterious effect on their mental well-being ( Saw et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%